Improving the compact heat exchangers with profiled tubes for marine power plants. Issue 1 (1st January 2022) - Naumenko, A V; Lychakov, V D; Egorov, M Yu; Shcheglov, A A; Matyash, A S; Borisov, A O; Balunov, B F
Abstract: The design features of heat exchangers with flat tubes are considered. The stages of creating a new flat tube and its prototypes are analyzed. An oil refrigerator is chosen as a prototype of the heat exchanger because of the previous use of flat tubes with wells, now replaced with new flat profiled tubes. Thermal and hydraulic tests of a refrigerator made of such tubes are carried out at the stand. During the testing, the hydraulic resistance of the cavities of the cooled and cooling media and thermal parameters are determined: heat power, heat transfer coefficient and heat transfer coefficient from the cooled medium in the inter-tube cavity with the transverse flow of tubes to the tube wall. A satisfactory correspondence of the actual power values determined for both working environments has been established. The discrepancy does not exceed (-7.6%)-(+5%) with an average value of +0.2%. A satisfactory correspondence of the actual and calculated values of the refrigerator power has been obtained. The discrepancy does not exceed (-15%)-(+9%) with an average value of -2.8%. The calculation of the capacity of the refrigerator during its operation in the design mode of oil cooling is carried out. The oil flow is considered both through the pipe and through the inter-pipe space. A good convergence of the calculations with the experimental results has been revealed.